Effect analysis on cold starting performance enhancement of a diesel engine fueled with biodiesel fuel based on an improved thermodynamic model. (1st June 2019) - E, Jiaqiang; Liu, Guanlin; Zhang, Zhiqing; Han, Dandan; Chen, Jingwei; Wei, Kexiang; Gong, Jinke; Yin, Zibin
Graphical abstract: Highlights: Cold starting process of diesel engine at low temperature is analyzed in detail. An improved thermodynamic model of diesel engine is developed. Cold starting performance of diesel engine is validated by the experimental results. Suggestions for cold starting performance enhancement of the diesel engine are proposed. Abstract: It is very important for the diesel engine to achieve a cold startup at low environmental temperature especially in the region with the temperature in the range of −40 °C to 0 °C. Thus, the specific cold start characteristics, such as gas leakage, heat loss and clearance volume, should be investigated in detail. In order to investigate the cold start ability, an improved thermodynamic model for thermodynamic parameters is developed. The prediction of ignition temperature is the closest to the experimental values when the adiabatic index is equal to 1.34 for the compressed gas. The thermodynamic results show that the compression pressure is the most sensitive to the gas leakage rate, followed by the heat transfer loss rate and reference clearance volume. The gas leakage, heat loss and clearance volume are employed to investigate the cold start ability for the diesel engine, which provide a better reference for strengthening the cold start capacity research. The small clearance volume and big initial intake air temperature can improve the exergy of diesel engine. In addition, the entropy production increases with the increase of clearance volume. Similarly, the exergy of system will reduce with the increase of entropy production. Finally, the improvement suggestions for cold starting performance enhancement of the diesel engine are proposed.